Warfare and Tracking in Africa, 1952-1990, Timothy J. Stapleton - Kleynhans, Evert (Scientia militaria : South African journal of military studies, 2016)
Tracking is defined as “the ability to pursue and close with an animal or human subject by following signs … left behind in the environment” (page 1). The post-1945 wars of decolonization in Africa were largely characterised by guerrilla campaigns fought by nationalist movements bent on expelling or overthrowing European colonial rulers or white minority settler regimes. The security forces which operated against the nationalist insurgencies, employed a number of counterinsurgency methods to find the elusive guerrillas who often had their staging areas in remote, uninhabited, areas. Tracking was one of the methods used during these counterinsurgency operations to locate and engage insurgents. The use of tracking in counterinsurgency warfare is, furthermore, largely determined by the local geography, technology and colonial culture of each specific military operating environment (pages 2, 137).